SAMPLE PREPARATION AND BIOANALYSIS VALIDATION FOR NATURAL PRODUCT SAMPLE - AYUMIATI, IDA; SAPUTRI, FEBRINA AMELIA; MUCHTARIDI, MUCHTARIDI (International Journal of Applied Pharmaceutics, 2021)
Bioanalysis study and its validation are important for the application in natural drug discovery and preparation for natural medicine products with safe drug development approaches. Bioanalysis data for natural products can provide quantitative information on active compounds from natural products for pharmacokinetics, pharmacodynamics, bioavailability, bioequivalence, and toxicokinetics. Bioanalysis validation provides useful guidance for obtaining accurate data on drug discovery, preclinical and clinical testing of natural drug product development, and to ensure the methods used are suitable for application in testing the samples. In general, sample preparation and validation of the bioanalysis method are part of the pharmacokinetic characterization of a chemical compound from the discovery to the development stage of natural material products. Therefore, this paper aims to discuss how to prepare samples and validate bioanalysis for natural products.